The Rise and Fall of Dagong Global Credit Rating Agency: A Geopolitical Challenge for the Rating Industry. Issue 2 (29th June 2021) - Bush, Chunping
ABSTRACT: Dagong Global Credit Rating Agency (Dagong) was originally branded as a Chinese national representative credit rating agency. Its international expansion in the US and the EU, in order to challenge the biggest international credit rating agencies, was unsuccessful and achieved little of significance. Dagong's business suffered a complete halt because of a one-year suspension by the Chinese financial regulators. Its ratings heeded China's geopolitical interest and China's strategic plans of economic development rather than signalling the credit risks of debt instruments. Dagong's ratings had a significant political bias towards countries which were China's economic and political allies or supplied raw materials to China. Dagong officially became a state-owned credit rating agency following a reconstruction by the Chinese state in 2019. This article concludes that this new ownership may exacerbate the geopolitical characteristics of Dagong and poses a challenge to the international financial market.